Attenuated total reflectance infrared spectroscopy as a screening tool for the urinary calculi characterization. - Capella Torres, A.; Pérez Guaita, D.; Ventura Gayete, J.; Sancho Andreu, M.; Garrigues, S.; de la Guardia, M. (Ciencia)
The aim of this study has been the development of a fast and reduced cost screening tool for the kidney stones characterization based on attenuated total reflectance infrared measurements (ATR-FT-IR) and hierarchical cluster analysis (HCA). The method was compared with the traditional chemical methods used in hospitals based on reagents kits. 111 renal calculi samples were analyzed by a reference chemical method and their infrared ATR spectra obtained. The cluster analysis was made using the regions from 3662 to 2247 cm-1 and from 1956 to 565 cm-1 after vector normalization of spectra data and using Ward”™s linkage method and the Euclidean distance for the discrimination of the different sample groups. Dendrographic classification provides four groups of samples, according to the presence of uric acid, calcium oxalate or a combination of this compound with other phosphate salts. The IR spectra and dendrographic classification evidences the bad discrimination of some stone samples by the chemical method. As a conclusion, hierarchical cluster analysis of ATR-FT-IR spectra of kidney stones provides a fast, low-cost and environmental friendly method to classify samples in order to establish the clinical origin of urinary calculi, being evidenced that this methodology is free from the mistakes found in some cases using chemical kits.